1999
DOI: 10.2135/cropsci1999.0011183x003900010041x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity among Selected Vigna angularis (Azuki) Accessions on the Basis of RAPD and AFLP Markers

Abstract: Genetic diversity within the azuki Vigna angularis (Willd.) Ohwi and Ohashi genepool has not been extensively examined with molecular markers. The objectives of this study were to: (i) use RAPD and AFLP analyses to assess the genetic similarity among selected azuki accessions from distinct production regions in Asia, and( ii) compare the utility of the two DNA marker systems for evaluating similarity. Results also will provide information for parental selection in a breeding program. Fifty‐seven RAPD and 214 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
34
0
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(46 citation statements)
references
References 0 publications
8
34
0
4
Order By: Relevance
“…Gajera et al (2010) reported that dendrograms showed no clear pattern of clustering according to the locations from where genotypes were collected, indicating little or no location specificity among castor genotypes. Similar results were also reported in Azuki bean (Yee et al, 1999) and in groundnut (Dwivedi et al, 2001). The high genetic diversity observed implies that an appropriate and efficient protection strategy if employed would help restore the species stability to a significant extent.…”
Section: Discussionsupporting
confidence: 84%
“…Gajera et al (2010) reported that dendrograms showed no clear pattern of clustering according to the locations from where genotypes were collected, indicating little or no location specificity among castor genotypes. Similar results were also reported in Azuki bean (Yee et al, 1999) and in groundnut (Dwivedi et al, 2001). The high genetic diversity observed implies that an appropriate and efficient protection strategy if employed would help restore the species stability to a significant extent.…”
Section: Discussionsupporting
confidence: 84%
“…Estes resultados sugerem que genótipos distintos têm sido utilizados na implantação dos pomares de acerola. Yee et al (1999), analisando acessos de Vigna angularia, observaram igualmente ausência de correlação entre grau de similaridade genética obtida com base em marcadores de DNA e procedência dos acessos. Neste caso, os autores apontam para a possibilidade de que a origem dos acessos difere do local de coleta.…”
Section: Análise Genética Dos Marcadores Rapdunclassified
“…It has following economic importance: environmental (soil improver as a green manure), animal food (forage), medicines (folklore-herb) and for human food (pulse, vegetables, beverage base) (Sato et al, 2005). The ability of adzuki bean to grow in different geographical regions brought the opportunity for introducing this legume into Serbian agricultural practice (Yee et al, 1999;Zong et al, 2003). Adzuki bean has high physiological nitrogen (N) requirements.…”
Section: Introductionmentioning
confidence: 99%